Faktor Resiko yang Berhubungan dengan Kejadian Infeksi Menular Seksual (IMS) di Klinik Voluntary Counseling Test (VCT) - Refti, Weni Guslia (Universitas Aisyah Pringsewu, 2018)
The prevalence of Sexually Transmitted Infections (STIs) in Indonesia tends to increase. Recorded in 2011 were 11,280 cases consisting of 5,131 (45.4 percent) of ghonorrhea cases, 4725 (41.8 percent) of syphilis cases and 1424 (12.8 percent) of HIV-AIDS cases. In 2012 there was an increase of 13,043 cases consisting of 6003 cases of ghonorrhea (46 percent), syphilis as many as 5216 cases (40 percent) and HIV / AIDS as many as 1824 cases (14 percent). This study aims to provide an overview of risk factors associated with STI events in society objectively. This type of research is quantitative with crossectional approach, using primary data from interview result. The population is all patients who conduct examination at clinic of Voluntary Counseling Test (VCT) Bob Bazar Public Hospital Kalianda Lampung as many as 551 people. The sample of this study as many as 143 people. Sampling using Accidental sampling technique. Data analysis uses frequency distribution, chi square and logistic regression. The results showed that there was a correlation between STI event with age (p = 0,020, OR = 2,35), education level (p = 0,006; OR = 2,71), gender (p = 0,023; OR = 2,35) (p = 0,009; OR = 2,56), socioeconomic level (p = 0,015; OR = 2,43), and marital status (p = 0,001; OR = 0.001; OR = 5.35). Continuous monitoring and dissemination of appropriate and correct information on STIs can be done as a precaution by coordinating and collaborating with BKKBN, PKBI, NGOs and Ministry of Religious Affairs.